LARANGAN PERNIKAHAN SESUKU SEKAMPUNG SEPUCUK ADAT DIKENAGARAIAN AIA MANGGIH KABUPATEN PASAMAN SUMATERA BARAT - Aci Lovita Sari; Zulfikar Jaya Kusuma; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Custom is a reflection of the personality of a nation, is one of theincarnations of the soul of the nation concerned from century to century. For thepeople of Indonesia, the law that becomes the benchmark for behavior iscustomary law. Customary law is considered as a rule of life to achieve peace insociety. One of the rules in customary law is marriage.Marriage is a spiritual bond between a man and woman as husband andwife with the aim of forming a happy and eternal family based on the Godhead ofthe Almighty. However, not all marriages can be carried out even though theyhave fulfilled the agreed terms and conditions. In Kenagarian Aia M Advanced,Pasaman Regency, West Sumatra, there was a prohibition on marriage to atribe as a traditional village. The existence of this prohibition is caused by severalfactors and also some very bad effects for the perpetrators, families and even theirdescendants later. The formulation of the problem in this thesis, namely: First,what are the factors causing the prohibition of marriage to a tribe of a village inthe Kenagarian Aia M Advanced Pasaman Regency, West Sumatra? Secondly, arethere any limits on the level of heredity for the prohibition of marriage to a tribeof a tribe in Kenagarian Aia M Sophisticated, Pasaman, West Sumatra?This type of research used is a type of sociological juridical research,because in this study directly conducted research at the site in order to provide acomplete and clear picture of the problem under study. This research wasconducted in Kenagarian Aia M Advanced Pasaman Regency, West Sumatra,while the population and sample were all parties concerned with the problemsexamined in this study, the data sources used, primary data, secondary data andtertiary data, data collection techniques in this study with interview and literaturestudy. From the results of the study, there are three main things that can beconcluded..Keywords: Sesuku Marriage, Prohibition